Generalized Anhidrosis: A Rare Dermatological Condition (Bangladesh Medical Journal, 2014)
Anhidrosis is the inability of the body to produce and /or deliver eccrine sweat to the skin surface in response to an appropriate stimulus or environment. It may be due to changes in the eccrine sweat gland, alterations in the nervous pathway or due to metabolic, endocrine or systemic disease. Purely psychogenic anhidrosis is also known. Occasionally it may not be possible to identify the cause. It may be localized, generalized, partial or complete. Extensive anhidrosis may impair heat regulation and produce heat exhaustion. The pathogenesis and underlying lesion of acquired idiopathic generalized anhidrosis (AIGA) are apparently heterogeneous. Acquired idiopathic generalized anhidrosis (AIGA) is a rare disorder in which systemic anhidrosis occurs in the absence of any causative skin, metabolic or neurological disorder. Congenital insensitivity to pain and anhidrosis (CIPA), also known as hereditary sensory and autonomic neuropathy type III is an autosomal recessive disorder characterized by the congenital lack of pain sensation, inability to sweat, episodes of recurrent hyperpyrexia. mental retardation, and self-mutilating behavior. It is due to mutations in the neurotrophic lyrosine receptor kinase I (NTRK1) gene in chromosome. DOI: http://dx.doi.org/10.3329/bmj.v41i3.18962 Bangladesh Medical Journal 2012 Vol.41(3): 57-58